Territoriality in Drosophila: indirect effects and covariance with body mass and metabolic rate. (3rd April 2021) - Tremblay, Matteo; Rundle, Howard D; Videlier, Mathieu; Careau, Vincent
Abstract: Territoriality (i.e., defense of a resource) is the outcome of behavioral interactions that can result in selective advantages in many vertebrates and invertebrates. Since territoriality is expressed in a social context, an individuals' territoriality may change according to the phenotype of the opponents that they are confronted with (termed "indirect effects"). Defending a territory may also confer energetic costs to individuals, which could be reflected in their standard metabolic rate (SMR), a key component of an ectotherms' energy budget. Here, we measured territoriality using dyadic contests, body mass, and SMR using flow-through respirometry, twice in each of 192 adult male Drosophila melanogaster . Territoriality, body mass, and (whole-animal) SMR were all significantly repeatable. However, essentially all the among-individual variation in SMR was shared with body mass, as indicated by a very strong among-individual correlation ( r ind ) between body mass and SMR. The among-individual correlation between territoriality and SMR also tended to be positive, suggesting the presence of underlying metabolic costs to territoriality. Although indirect effects on territoriality were present but weak (accounting for 8.4% of phenotypic variance), indirect effects on territoriality were negatively and significantly correlated with body mass. This indicates that larger individuals tended to suppress their opponents territoriality. Variation among individuals in their ability to suppress territoriality in others was not associated with their own territoriality or SMR. Abstract : Larger flies suppress territoriality in others by excluding them from a resource. Using repeated pairwise encounters over a food resource, we quantified the extent to which individual males differ in territoriality, body mass, metabolic rate, and how they influence territoriality in others. More territorial individuals tend to have higher metabolism. Large individuals are either better at excluding others from the resource, or they are more motivated to do so given their higher energetic requirements, compared to smaller individuals.